[Rezension von: Afterlives of ancient rock-cut monuments in the Near East : carvings in and out of time] - Bilgin, Tayfun ca. 20./21. Jh.; Carvings in and out of time : afterlives of rock-cut monuments in the Ancient Near East 2017 Providence, RI (2023)
Afterlives of Ancient Rock-cut Monuments in the Near East: Carvings in and out of Time. Edited by Jonathan Ben-Dov and Felipe Rojas Culture & History of the Ancient Near East, vol. 123. Leiden: Brill, 2021. Pp. xxiii + 441. $190.
Keywords: Rezension